2016
DOI: 10.1097/ncc.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Family Members Older Than 50 Years of Turkish and Northwest African Descent

Abstract: This study provides new insights into the moral and practical meaning of caregiving, which will help professionals understand the roles adopted by family members. Furthermore, individualized approaches to care appear to be essential, because concrete ideas about informal caregiving differ strongly despite shared values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…[33][34][35][36] However, recent evidence shows that shared cultural and religious values may not predict day-to-day care practices by family members of patients over 50 years who have cancer. 37 Indeed, some studies suggest that sociocultural characteristics that influence medical decision making in general and FI in particular may vary within cultures across families and individuals. 6,11 Such findings indicate that the literature may have neglected ''deeper concepts'' involved in triadic (physician-patient-family) medical consultations.…”
mentioning
confidence: 99%
“…[33][34][35][36] However, recent evidence shows that shared cultural and religious values may not predict day-to-day care practices by family members of patients over 50 years who have cancer. 37 Indeed, some studies suggest that sociocultural characteristics that influence medical decision making in general and FI in particular may vary within cultures across families and individuals. 6,11 Such findings indicate that the literature may have neglected ''deeper concepts'' involved in triadic (physician-patient-family) medical consultations.…”
mentioning
confidence: 99%
“…Participant 3 described how having other family members around helped her, and used the metaphor of an "army" to describe the power of support she felt by their presence. Similarly, van Eechoud et al [36] in a study that involved Muslim family caregivers of Arab and Turkish origin documented that caregiving tasks were shared between family members.…”
Section: Discussionmentioning
confidence: 99%
“…A finding that relates to caregivers lack of preparedness and feelings of fear, anxiety, stress, inadequacy and uncertainty about their ability of providing home care. [20,[35][36][37][38][39] Furthermore, the literature affirmed that there was no discussion about what to expect in palliative home care and carers felt health professionals were hesitant to discuss difficult issues like managing palliative care at home and end of life care. [40] Thus, they learned caregiving skills by trial and error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier paper, concerning the meaning of caregiving, we reported that cancer is considered a family matter and caregiving had a strong meaning, both moral and practical, for all participants (van Eechoud et al . ). In particular, adult children felt a deeply moral obligation towards caring for the sick parent.…”
Section: Introductionmentioning
confidence: 97%